Interference factors in process and tissue donation of organs: review of literature - Brito, Livia Diederichsen de; Prieb, Rita Gomes (Brazilian Journal of Transplantation, 2012)
Organ and tissue transplantation is an increasingly common practice in medical routine. In Brazil, to donate the only requirement is the relatives’ consent. However, the amount of donation is often reduced due to some barriers. Purposes: By a literature review aimed to identify factors affecting the consent of relatives of the dead body of potential donors after brain death in the process of organ donation. In addition, we seek to identify what conditions it is appropriate to deal with the families of potential donors and also to evaluate the effect of bad news on the consent of organ and tissue donation. Methods: The study was conducted through a literature review using the OvidMedline database using the keywords “organ” or “tissue” and “don*” or “consent”, from June 2008 to May 2012. The search was limited to articles published in Portuguese and English and that included adult humans. Results and Discussion: The factors to refuse consent most cited were difficulty in understanding the diagnosis of brain death, ignorance of the deceased’s wishes about organ donation, the family’s desire to preserve the integrity of the body of the deceased, divergence of opi- nions among the families about the donation, the scarce time for the decision to donate and the failure in communication between the family and the health care professional. The setting for discussion is not set up as interference factor for donation but it was only highlighted the importance of conducting the interview in a private location. Conclusion: Organ transplantation is establishing itself as a practice that gives hope of a new condition of life for thousands of people who have various dysfunctions. However, for this to occur, it is important that organ harvesting is effective. Several factors are cited as possible refusal as above. For that reason, to increase the rate of donation, it is important that a team of skilled and qualified professionals is that not only provides a forum for continence, but also addressed the host family. Furthermore, communication between team members and family members must be effective, thus favoring the intention of donation.